2015
DOI: 10.1371/journal.pone.0145660
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Aphid Infestation Induces Changes in Fatty Acid Metabolism in Soybean

Abstract: The soybean aphid (Aphis glycines Matsumura) is one of the most important insect pests of soybeans in the North-central region of the US. It has been hypothesized that aphids avoid effective defenses by inhibition of jasmonate-regulated plant responses. Given the role fatty acids play in jasmonate-induced plant defenses, we analyzed the fatty acid profile of soybean leaves and seeds from aphid-infested plants. Aphid infestation reduced levels of polyunsaturated fatty acids in leaves with a concomitant increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 67 publications
0
27
0
Order By: Relevance
“…The fatty acid substrate of the JA pathway is α-linolenic acid (18:3), which is produced from galactolipids of chloroplast membranes (Wasternack and Hause, 2013). Recently Kanobe et al (2015) detected less α-linolenic acid in soybean plants ( G. max ) infested with the soybean aphid ( Aphis glycine ) than in uninfested control plants or plants infested with other soybean antagonists, the soybean cyst nematode ( Heterodera glycines ) and the brown stem rot ( Cadophora gregata ). This suggests that certain pea aphid clones might suppress one of the steps in JA signaling or biosynthesis prior to the formation of α-linolenic acid.…”
Section: Discussionmentioning
confidence: 99%
“…The fatty acid substrate of the JA pathway is α-linolenic acid (18:3), which is produced from galactolipids of chloroplast membranes (Wasternack and Hause, 2013). Recently Kanobe et al (2015) detected less α-linolenic acid in soybean plants ( G. max ) infested with the soybean aphid ( Aphis glycine ) than in uninfested control plants or plants infested with other soybean antagonists, the soybean cyst nematode ( Heterodera glycines ) and the brown stem rot ( Cadophora gregata ). This suggests that certain pea aphid clones might suppress one of the steps in JA signaling or biosynthesis prior to the formation of α-linolenic acid.…”
Section: Discussionmentioning
confidence: 99%
“…oryzae-infected MoSDT1-transgenic rice Linolenic acid and linoleic acid are precursors of jasmonic acid synthesis [10]. In this study, these two metabolites and salicylic acid were identified to accumulate in M. oryzae-infected MoSDT1-transgenic rice at 72 h. Meanwhile, the contents of JA, JA-Ile, and salicylic acid were higher in infected transgenic rice than infected wild-type rice.…”
Section: Analysis Of the Induced Resistance Of Rice After Treatment Wmentioning
confidence: 60%
“…Linolenic acid and linoleic acid among lipids and lipid-like molecules, raffinose among organic oxygen compounds, tyramine among benzenoids, and unclassified alphapinene showed significant accumulation at 72 h. Oxalate among organic acids and derivatives decreased at 72 h and became undetectable at the other two time points. Anthranilic acid and dopamine in benzenoids were accumulated significantly at 0 h and 120 h. Organic oxygen compounds [9], lipids and lipid-like molecules [10], benzenoids [11,12], and many unclassified metabolites were detected in M. oryzae-infected MoSDT1-transgenic resistant rice. These are the core defense metabolites in M. oryzae-infected MoSDT1-transgenic plants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This process of hijacking plant defenses has also been observed in insect herbivores, including aphids (Hillwig et al 2016). Soybean aphid feeding can alter fatty acid metabolism and thereby affect the precursors to jasmonate-dependent defenses (Kanobe et al 2015). Another study showed some evidence that A. glycines can obviate plant defenses conferred by the Rag1 gene.…”
Section: Induced Resistance By Microorganismsmentioning
confidence: 83%